EVALUATING UI/UX OF PHONETICS AUGMENTED REALITY - Afriliani; Riyanto, Agus; Efendi, Yudi; Meri Dewi Pendit, Ni Putu; Widyasari; Mulyajati, Enggar; Ardianto, Ardik (Universitas Terbuka, 2024)
This study aimed to evaluate augmented reality of phoneme. This study followed an observation-discussion process in which the researcher provided applications and checklists to the participants. Participants were asked to operate the application and fill out a checklist where the researcher discussed the use of the application. The research results show that participants are satisfied with the UI display and want minor improvements so that the display is better and equipped with more complete information. while for UX, participants agreed that the application was easy to use and helped the learning process. From the trial, the researcher summarized several things that needed to be corrected and errors that had not been detected before, such as speech errors. The author presents follow-up results from the last part of AR application development. The results of this trial are the final stage which answers whether this application is feasible to be launched.